Golimumab and certolizumab pegol for the treatment of hidradenitis suppurativa: a literature review and future perspective - Amirhossein Heidari; Yekta Ghane; Nazila Heidari; Seyedayin Hosseini; Azadeh Goodarzi (SAGE Publishing, 2024)
Hidradenitis suppurativa (HS) is an inflammatory skin condition with an underlying inflammatory process. Due to the limited efficacy of available treatments, HS remains a therapeutic challenge. The safety and efficacy of tumor necrosis factor-α (TNF-α) inhibitors, adalimumab, infliximab, and etanercept, are well studied in this patient population, and in some cases, HS was unresponsive to them. In recent years, evidence has been growing regarding the application of other anti-TNFs, including certolizumab pegol (CPZ) and golimumab. We sought to evaluate the overall safety and efficacy of golimumab and CPZ in the management of HS. A comprehensive search was performed on the PubMed, Scopus, Web of Science, and Ovid Embase databases, as well as the Google Scholar search engine from initiation to 31 August 2023. A total of nine and four studies used CPZ and golimumab to treat HS, respectively. Individuals with concomitant inflammatory immune-mediated diseases, pregnant females, and patients who were refractory to previous treatments achieved a Hidradenitis Suppurativa Clinical Response following CPZ administration. Also, golimumab showed promise in treating recalcitrant HS after the failure of other treatments, such as adalimumab and anti-interleukin-1. CPZ and golimumab can be efficacious treatment options for moderate-to-severe HS, especially in patients who are unresponsive to other TNF inhibitors, such as adalimumab.